EVALUATION OF DIFFERENT NEWCASTLE DISEASE VIRUS VACCINATION REGIMES AGAINST CHALLENGE WITH RECENTLY ISOLATED GENOTYPE VII VIRUS FROM EGYPT - Mohamed M. Megahed; Wala Mohamed; Ola Adel Hassanin (Slovenian Veterinary Research, 2023)
Newcastle disease virus (NDV) genotype VII is incriminated in the currently circulating NDV outbreaks in the Middle East region. In this study, evaluation of different vaccination regimes including genetically-matched or mismatched vaccines to the currently circulating field virulent NDV (vNDV) genotype VII was performed. One-day-old Arbor Acres broiler chicks were divided into nine groups; groups 1 to 3 were vaccinated with live or inactivated genetic-mismatched vaccines (genotype II) or both of them. Groups 4 to 6 were vaccinated with either live or inactivated genetic-matched vaccine to vNDV genotype VII or combination of them. Group (Gp) 7 was vaccinated with a combination of inactivated genetic-matched and live genetic-mismatched vaccines to vNDV genotype VII  while groups 8 and 9 were kept as control non-vaccinated. The groups that received a combination of live and inactivated vaccines from either genetically-matched or mismatched origins had the highest serological responses and protection against mortality which was 100%. The two groups received a combination of inactivated genetic matched vaccine and live vaccines of either genetic-matched or mismatched origins had the lowest clinical index and were nearly completely protected against vNDV clinical signs. The virus tracheal and cloacal shedding titers and number of shedders were significantly reduced or nearly neglicable in the instance of application of inactivated genetic-matched vaccine to the challenge virus either alone or boosted with live genetic-matched or mismatched vaccine. In consistent inactivated genetic-matched vaccine inhibited the transmissibility of the challenged virus to contacted birds. We concluded from our results that application of NDV vaccination regimes included a combination of inactivated NDV genotype VII vaccine and live vaccine regardless of its genotype provides better clinical protection and minimize virus shedding and subsequently decrease transmissibility and virus load to the surrounding environment.